Analyzing the Evolution of Auditing and Financial Insurance: Tracking Developments, Identifying Research Frontiers, and Charting the Future of Accountability and Risk Management - Trinandari Prasetyo Nugrahanti (West Science Accounting and Finance, 2023)
This research employed a bibliometric analysis to examine the evolution of financial audit and insurance, identify key developments, and determine research frontiers in the field. The analysis was conducted on a comprehensive dataset comprising scholarly articles, conference papers, and relevant publications. The data underwent preprocessing to ensure accuracy and reliability. Using VOSviewer, various analysis techniques were applied, including co-authorship analysis, citation analysis, and keyword and topic analysis. The findings revealed collaboration patterns among researchers, influential works, emerging research themes, and potential research frontiers. The results highlighted the impact of technological advancements, regulatory changes, and emerging risks on the field. The interpretation of the findings contributes to the understanding of accountability and risk management practices. The research identifies areas for further investigation, such as the integration of emerging technologies, regulatory effectiveness, and the management of emerging risks. The results provide insights into the past, present, and future trajectory of financial audit and insurance, guiding future research efforts and contributing to the advancement of accountability and risk management practices in the financial sector.